Differing ERP patterns caused by suction and puff stimuli. (6th May 2015) - Choi, Mi-Hyun; Kim, Hyung-Sik; Baek, Ji-Hye; Lee, Jung-Chul; Park, Sung-Jun; Jeong, Ul-Ho; Gim, Seon-Young; You, Ji Hye; Kim, Sung-Pil; Lim, Dae-Woon; Kim, Hyun-Jun; Chung, Soon-Cheol
Highlights: This study was compared ERP patterns for puff and suction stimuli (same intensity). For C3, the maximum and minimum latencies were reached earlier for the suction than for the puff. For FC5, maximum and minimum latencies were reached earlier for the suction than for the puff. The suction caused a more sensitive response in the somatosensory area (C3) than did the puff. The suction caused a more sensitive response in the motor area (FC5) than did the puff. Abstract: The present study compared event-related potential (ERP) patterns for two stimuli types, puff and suction, by applying these stimuli to the fingers; ERP patterns for the two stimuli were compared at C3, an area related to somatosensory perception, and at FC5, an area related to motor function. Participants were 12 healthy males in their 20 s (mean age = 23.1 ± 2.0 years). One session consisted of a Control Phase (3 s), a Stimulation Phase (3 s), and a Rest Phase (9 s). During the Stimulation Phase, a 4-psi suction or puff stimulus was applied to the first joint of the right index finger. After completion of the session, a subjective magnitude test was presented. In all phases, electroencephalography signals were recorded. We extracted maximum positive amplitude and minimum negative amplitude as well as relevant latency values for C3 and FC5 signals. Suction and puff stimuli had similar subjective magnitude scores. For both C3 and FC5, the maximum and minimum amplitude latency was reached earlier for the suction stimulus than for the puff stimulus. In conclusion, when suction and puff stimuli of the same intensity were applied to the fingers, the suction stimulus caused a more sensitive response in the somatosensory area (C3) and motor area (FC5) than did the puff stimulus.